2020
DOI: 10.1088/1361-6463/aba3ed
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence reveals micro discharge as a potential triggering factor for surface flashover

Abstract: The undetermined surface flashover of insulators limits the development of ultra-high voltage AC gas insulated equipment. In this paper, we report a micro discharge potentially triggered surface flashover phenomenon, which is revealed directly by luminescence activities of samples with different micro morphologies. The results show that sandblasted samples, which are prone to a lower surface flashover voltage, present luminescence pulses corresponding to micro discharge activities over the surface. Polished sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Besides, in 2020, Lin et al measured the luminescence curve of epoxy with metal oxide sandblasted. Result verifies that the micro discharge pulses easily generates on it [19]. Remarkably, the long-term surface discharge by micron metal particles is bound to degrade the surface structure and insulation characteristics on surface.…”
Section: Introductionsupporting
confidence: 55%
“…Besides, in 2020, Lin et al measured the luminescence curve of epoxy with metal oxide sandblasted. Result verifies that the micro discharge pulses easily generates on it [19]. Remarkably, the long-term surface discharge by micron metal particles is bound to degrade the surface structure and insulation characteristics on surface.…”
Section: Introductionsupporting
confidence: 55%
“…While for the AC surface flashover, the discharge voltage is too low to cause enough partial discharge in the solid, and thus partial discharge between protrusion and gas is the potential to trigger AC surface flashover. Lin [133] used luminescence techniques to detect partial discharge before AC flashover and found that the AC flashover voltage drops with the increase of the number of partial discharges before flashover. In the last 5 years, some scholars have focused on the effects of metal particles on GIS/GIL, and they also found that the partial discharge induced by metal particles sufficiently drops the surface discharge voltage [134,135].…”
Section: Essential Factors For Triggering Surface Flashovermentioning
confidence: 99%
“…Lin [133] investigated the effects of micro-discharges on AC surface flashover and found that the variation of surface roughness induces a large number of shallow traps, and the surface flashover voltage increases with the reduced trap level.…”
Section: Effects Of Surface Traps On Surface Flashovermentioning
confidence: 99%
“…They believed that the surface of the sample becomes flatter after fluorination, thereby the micro plasma activities due to the concentration of the electric field on the surface alumina edges and corners at the gas-solid-conductor triple junction are suppressed. They emphasized that these micro-discharges are likely to be a potential consequence of surface heteropolar charges and can thereby increase the possibility of undetermined surface flashover under both AC and DC voltage, which were also discussed in their follow-up research work [14,79]. In 2017, the physical mechanism of fluorination on carrier migration and the impact on flashover voltage were explored and the inhibitory effect of fluorination on surface discharge corrosion was preliminary studied( as shown in Figure 8(a)) [35].…”
Section: Researches In University Of Southamptonmentioning
confidence: 99%